(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: The study was conducted to find out any alterations in thyroid function status in first half of pregnancy (up to 20 weeks), with ultimate aim of deciding the usefulness of routine screening of thyroid function in pregnancy. Material and methods: A cross-sectional study was conducted in the department of Obstetrics & Gynaecology, Dhaka Medical College and Hospital, Dhaka, Bangladesh, over a period of one year from July 2011 to June 2012 on pregnant women in their 1st half of pregnancy to screen for the thyroid function. Based on predefined eligibility criteria, a total of 230 pregnant women were purposively included in the study. Thyroid function status was assessed by measuring serum levels of TSH, free thyroxine (FT4), and free tri-iodothyronine (FT3). Women with thyroid disorders were excluded. Results: The mean age of the patients being 24 years. Over 90% of the women were housewife and majority (88.7%) was educated. Over one-quarter of women was overweight with mean body mass index being 22.1 ± 4.4 kg/m2. The women were predominantly multigravida with 56% in 1st trimester 44% in the 1st half of 2nd trimester of pregnancy (13-20 weeks). Based on trimesters specific range of serum TSH in the 1st and 1st half of 2nd trimester (13-20 weeks) of pregnancy,13% of the patients were hypothyroid and 3% were hyperthyroid thus yielding a total of 37(16%) pregnant women with abnormal thyroid function status. Conclusion: The study concluded that one in every six women may have thyroid disorder in the first half of pregnancy and subclinical hypothyroidism is four times more common than the subclinical hyperthyroidism. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(1) : 26-31